The expression of inflammatory genes in human brain endothelial cells stimulated by beta-amyloid peptides is mediated by JNK-AP1 signaling pathway - Vukic, Vanja (University of Ottawa (Canada), 2008)
Alzheimer's disease (AD) is characterized by accumulation and deposition of beta-amyloid (Abeta) peptides in the brain. Deposition of Abeta peptides in cerebrovascular system results in chronic vascular inflammation, neurovascular uncoupling and insufficiency, contributing to neurodegeneration. The purpose of this study was to investigate the inflammatory response in human brain endothelial cells (HBEC) induced by aggregated Abeta 1-40 and the molecular mechanism of the Abeta-stimulated inflammatory gene expression. Primary or immortalized HBEC (iHBEC) were treated with aggregated Abeta1-40, control peptides (scrambled Abeta1-40 or poly-asparagine) or 2mM NaOH (vehicle), in the presence or absence of a specific JNK inhibitor (SP600125, 30 muM) at different time points, and inflammatory gene expression was analyzed by reverse-transcriptase polymerase-chain reaction (RT-PCR). TranSignal Protein/DNA Array was used to profile the activities of transcription factors (TF) in Abeta-stimulated HBEC. Nuclear extracts were isolated to determine interaction of AP-1 with DNA by electrophoretic mobility shift assay (EMSA) and supershift assay. The levels of total c-Jun and phosphorylated c-Jun at Ser73/Ser63 were analyzed through Western blotting, and AP-1 transcriptional activity was evaluated by reporter gene assays. In addition, to test indirect effects of Abeta on iHBEC, conditioned media from Abeta1-42-stimulated primary microglia was used to treat iHBEC at different time points in the presence of SP600125. The results obtained in this study have shown that aggregated Abeta1-40 peptides strongly stimulated the expression of monocyte chemoattractant protein 1 (MCP-1), interleukin 8 (IL-8), interleukin 6 (IL-6) and growth-related oncogene (GRO). TF profiling has revealed that Abeta treatment strongly activated AP-1 in the cells. Electrophoretic migration shift assay (EMSA) and supershift assay have confirmed that AP-1 was strongly activated in HBEC at 2 and 4 h post-Abeta-treatment and physically interacted with AP-1-binding DNA sequence and that c-Jun is a component of the activated AP-1 dimeric complex. Abeta-stimulated AP-1 activity was further confirmed by reporter gene assay. In summary, these experiments have demonstrated that binding and internalization of Abeta peptides at HBEC cellular membrane, possibly through RAGE, stimulated JNK signaling cascade pathway in HBEC which resulted in increased phosphorylation of c-Jun at Ser-73 and that activated AP-1 was responsible for increased expression of inflammatory genes in the cells. Aside from direct action on HBEC, Abeta peptides also stimulated microglia to release pro-inflammatory factors, which in turn, stimulated the expression of inflammatory genes in HBEC. The JNK-AP1 signaling pathway and inflammatory factors characterized in this study may potentially serve as therapeutic targets to relieve Abeta-induced inflammation in Alzheimer's disease. (Abstract shortened by UMI.)
Keywords: Biology, Neuroscience.; Biology, Cell.